1992
DOI: 10.1111/j.1471-4159.1992.tb08913.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatases 1 and 2A Dephosphorylate B‐50 in Presynaptic Plasma Membranes from Rat Brain

Abstract: The protein B-50 is dephosphorylated in rat cortical synaptic plasma membranes (SPM) by protein phosphatase type 1 and 2A (PP-1 and PP-2A)-like activities. The present studies further demonstrate that B-50 is dephosphorylated not only by a spontaneously active PP-1-like enzyme, but also by a latent form after pretreatment of SPM with 0.2 mM cobalt/20 micrograms of trypsin/ml. The activity revealed by cobalt/trypsin was inhibited by inhibitor-2 and by high concentrations (microM) of okadaic acid, identifying it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…However, it is possible that the extensive fractionation procedures used removed PP2A from these fractions. In agreement with the present study, Han et al (1992) have found that 135% of the phosphorylase phosphatase activity in rat synaptic plasma membranes can be attributed to PP2A and PP2A could be detected in these membranes by blotting with antipeptide antibodies specific to PP2A. We have also confirmed that the PP2A detected in the particulate fraction of the present study is most concentrated in membranes of neuronal origin (A. T. R. Sim et al, in preparation).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, it is possible that the extensive fractionation procedures used removed PP2A from these fractions. In agreement with the present study, Han et al (1992) have found that 135% of the phosphorylase phosphatase activity in rat synaptic plasma membranes can be attributed to PP2A and PP2A could be detected in these membranes by blotting with antipeptide antibodies specific to PP2A. We have also confirmed that the PP2A detected in the particulate fraction of the present study is most concentrated in membranes of neuronal origin (A. T. R. Sim et al, in preparation).…”
Section: Discussionsupporting
confidence: 93%
“…The association of high levels of PP2A with membranes specifically in brain implies unique roles for this phosphatase in this tissue. PP2A associated with the synaptic plasma membrane has been reported to contribute to a substantial proportion of the dephosphorylation of the neuronal phosphoprotein B-50 (Han and Dokas, 199 1;Han et al, 1992). Because we have now shown high levels of PP2A in these structures, it is likely that mechanisms responsible for the activation of PP2A will be of some consequence to the dephosphorylation, and therefore function, of this and other substrate proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Immunolocalization studies using C subunit-specific antibodies (Mumby et al ., 1985 ;Saitoh et al ., 1989) provided the first direct evidence for the presence of PP2A in brain and nerve terminals . Han et al . (1992) have recently demonstrated that PPIand PP2A-like activities present in SPMs are responsible for dephosphorylating neuromodulin .…”
Section: Discussionmentioning
confidence: 99%
“…(1987) subsequently demonstrated that brain protein phosphatases (tentatively identified as type 1 and 2A by inhibitor and substrate preferences) could catalyze this dephosphorylation . Although the presence of PP2A catalytic subunit has been demonstrated in brain and at nerve terminals by immunodetection (Saitoh et al, 1989, Han et al, 1992, the corresponding holoenzyme has not been fully characterized.…”
mentioning
confidence: 99%
“…Palmitoylation of Cys-3 and/or Cys-4 of B-50 is important for its plasma membrane-association and is not required for its phosphorylation by PKC. In vitro, B-50 has been reported to bind calmodulin and actin, to serve as a substrate for several kinases and phosphatases, to affect polyphosphoinositol metabolism by inhibiting phosphatidylinositol 4-phosphate (PIP) kinase, and to augment the binding of GTP-7-S to hetrotrimeric GTPbinding proteins G o and G i (reviewed by Liu and Storm [45]; Strittmatter et al [59]; De Graan and Gispen [24] [34,44,58].…”
Section: B-50/gap-43mentioning
confidence: 99%